First-row transition metal complexes of a phosphine-silylene- based hybrid ligand - Akhtar, Ruksana; Kaulage, Sandeep H.; Sangole, Mayur P.; Tothadi, Srinu; Parvathy, Parameswaran; Parameswaran, Pattiyil; Singh, Kirandeep; Khan, Shabana (Inorganic Chemistry, 2022)
We have prepared two new silylene-phosphine-based hybrid ligands Si{N(R)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)} [R = TMS {trimethylsilyl} (1) and TBDMS {tert-butyldimethylsilyl} (2)], which possess two donor sites. Furthermore, the treatment of the bidentate ligand 1 with base metal halides {FeBr2, CoBr2, NiCl(2)middotdme [nickel chloride(II) ethylene glycol dimethyl ether]} and 2 with NiBr(2)middotdme [nickel bromide(II) ethylene glycol dimethyl ether] afforded four-coordinate six-membered metal complexes 3-6, respectively, which feature coordination from both Si(II) and P(III) sites. Subsequently, complexes 3 [(FeBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 4 [(CoBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 5 [(NiCl2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], and 6 [(NiBr2)Si{N((SiBuMe2)-Bu-t)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}] are studied for their redox and magnetic properties with the help of UV-vis spectroscopy, cyclic voltammetry, SQUID magnetometry, and theoretical calculations. Complexes 3-6 were found to display a paramagnetic behavior. All the compounds are well established by single-crystal X-ray diffraction studies.

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Smallest acyclic tricationic molecule containing a Bis(phosphine)-stabilized low-valent triantimony-based Unit - Mukherjee, Nilanjana; Peerless, Benjamin; Nadurata, Vincent L.; Kumar, Vikas; Sangole, Mayur P.; Singh, Kirandeep; Wiedemann, Haakon T. A.; Kay, Christopher W. M.; Kruk, Robert; Weigend, Florian; Dehnen, Stefanie; Gonnade, Rajesh G.; et al. (Nature Communications, 2026)
Element-element bonded multiply charged cationic species are well known as dimers or small cyclic oligomers in the condensed phase. However, the smallest acyclic version, a trinuclear unit possessing greater than a monocationic charge, has remained elusive. Here we introduce a bis(phosphine) supported low valent triantimony-based tricationic compound as a new entrant in this field. Structural elucidation and electronic understanding reveal a W-shaped tricationic unit comprising of a three-center four-electron sigma-bonded triantimony moiety that is terminally capped by bis(phosphine) ligands, with the central antimony atom having two lone pairs of electrons. The unique counter trianion [Sb(O)2(OTf)4]3- (OTf = CF3SO3) possesses reactive polar Sb delta+-O delta- bonds, the structure of which is determined from single crystal X-ray diffraction analysis. The ensemble of reactive molecular fragments found in this highly charged antimony-based compound makes it thermally unstable. Nonetheless, this fully characterized fleeting species shows a diverse reactivity profile, advancing the isolation of various novel antimony compounds, including the formation of a distinct low-valent antimony-cobalt carbonyl cluster.